Effectiveness of four topical treatment methods in a rat model of superficial partial-thickness burn injury: the advantages of combining zinc-hyaluronan gel with silver foam dressing. Issue 12 (December 2022) - Csenkey, Alexandra; Hargitai, Emma; Pakai, Eszter; Kajtar, Bela; Vida, Livia; Lorincz, Aba; Gergics, Marin; Vajda, Peter; Jozsa, Gergo; Garami, Andras
Highlights: A new rat model for superficial partial-thickness burns was developed. Comparative testing of four different treatment protocols was performed. Burn wound healing was evaluated at 5, 10, and 22 days post-injury. Combination therapy consisting of zinc-hyaluronan gel with a silver foam dressing was the most advantageous. Abstract: Background: There are several options available for conservative treatment of partial-thickness burns, however, reliable, affordable, and easily obtainable animal testing models are hard to find for the comparison of the different treatment methods. We aimed at developing a preclinical testing model and at comparing four treatment methods for superficial partial-thickness burns. Methods: Burn injury was induced in 90 adult male Wistar rats by placing the 130°C hot tip of a commercially obtainable soldering device for 30 s on the clipped skin of the interscapular region at a steady pressure. Skin histology was studied on days 5, 10, and 22 after the induction of the burn injury, on which days, respectively, the ratio of the not epithelialized wound (%), the extent of re-epithelialization (score), and the scar thickness (µm) were assessed. We compared 4 groups: silver-sulfadiazine cream, zinc-hyaluronan gel, silver foam dressing, and the combination of zinc-hyaluronan gel with a silver foam dressing. Results: On day 5, the induction of superficial partial-thickness burn injury was confirmed histologically in the rats. The zinc-hyaluronan gel and the combination treatment resulted in a markedly smaller ratio of the non-epithelialized area (29 ± 10% and 28 ± 13%, respectively) than silver-sulfadiazine cream (69 ± 4%; p < 0.01). On day 10, the extent of re-epithelialization was the lowest (∼0.2) in the silver-sulfadiazine cream group, while the other 3 treatments performed significantly better. The combination treatment lead to the maximal score of 2 in all rats, which was higher than in the other 3 treatment groups. On day 22, the scar thickness was the smallest in the combination treatment group (560 ± 42 µm), which was significantly less than in the silver-sulfadiazine cream group (712 ± 38 µm; p < 0.05). Conclusions: We designed and histologically confirmed a reproducible method for induction of superficial partial-thickness burns in rats for preclinical testing. In our model, the combination of zinc-hyaluronan gel with silver foam dressing was more effective than either of its components alone or than silver-sulfadiazine cream.